Boosting Business Activity of Supply Chain for Construction Companies - Oksana Skotarenko; Andrey Gafurov; Tatyana Belevskikh; Svetlana Bespalova; Natalya Shchebarova (International Journal of Supply Chain Management, 2018)
Boosting the business activity of the supply chain for construction companies is an important business problem for each state, as it provides accommodation for the population. This problem is particularly acute in countries that are experiencing an economic crisis, such as Russia. This article assesses the business activity of the supply chain for construction companies based on turnover indicators (2015-2017), as well as analyzing the company's liquidity to introduce areas to promote supply chain activity. For example, we took into consideration the economic indices registered in Snabstroy LLC, which specializes in deliverables for the installation of windows and doors. As a result, this document shows that a crisis has led to a decline in the business activities of the supply chain for construction companies. Russian state programs have succeeded in stopping businesses, but remain at a significantly lower level than the pre-crisis period. In this regard, this article introduces original recommendations on the increase in the business activity of the supply chain for construction companies. Key words- boosting, supply chain, turnover, business activity, construction companies, management.